1993
DOI: 10.1007/bf02246944
|View full text |Cite
|
Sign up to set email alerts
|

Autoshaping i.v. cocaine self-administration in rats: effects of nondrug alternative reinforcers on acquisition

Abstract: The purpose of this experiment was to examine the effects of a nondrug alternative reinforcer and feeding conditions on the acquisition of cocaine self-administration. Rats were autoshaped to press a lever that resulted in a 0.2 mg/kg i.v. cocaine infusion. Responses on the lever were monitored during six consecutive autoshaping sessions that occurred each day. A retractable lever was inserted into the operant chamber on a random time 60 s schedule 10 times per session for six sessions that began each hour. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 19 publications
4
117
2
Order By: Relevance
“…This preference shift occurred regardless of the dose of cocaine available and even following a long history of extended access to cocaine self-administration Cantin et al 2010). These findings are generally consistent with previous research (Carroll et al 1989;Carroll and Lac 1993) and with recent behavioral economics studies showing that food (or sucrose) demand was more inelastic than cocaine demand (Christensen et al 2008; Koffarnus and Woods 2011; for review, see Kearns et al 2011). They are also congruent with a recent study showing that mice preferred drinking sucrose over direct optostimulation of midbrain dopamine neurons (Domingos et al 2011).…”
Section: Drug Preference Over Nondrug Rewardssupporting
confidence: 90%
“…This preference shift occurred regardless of the dose of cocaine available and even following a long history of extended access to cocaine self-administration Cantin et al 2010). These findings are generally consistent with previous research (Carroll et al 1989;Carroll and Lac 1993) and with recent behavioral economics studies showing that food (or sucrose) demand was more inelastic than cocaine demand (Christensen et al 2008; Koffarnus and Woods 2011; for review, see Kearns et al 2011). They are also congruent with a recent study showing that mice preferred drinking sucrose over direct optostimulation of midbrain dopamine neurons (Domingos et al 2011).…”
Section: Drug Preference Over Nondrug Rewardssupporting
confidence: 90%
“…For example, Carroll and her associates have reported that pairings of the insertion of a lever CS with intravenous administration of drug reward US induced the automatic "shaping" of lever-pressing for drug self-administration in rats. Procedures of this sort have been employed to induce reliable leverpressing for the self-administration of the cocaine US (Carroll and Lac, 1993, 1998Specker et al, 1994;Gahtan et al, 1996;Lynch and Carroll, 1999;Lynch et al, 2001;Campbell and Carroll, 2001;Campbell et al, 2002;Carroll et al, 2002;Roth et al, 2002; see also Panlilio et al, 1996;Weiss et al, 2003 c.f., Di Ciano andKearns and Weiss, 2004), orthe self-administration of the amphetamine US (Carroll and Lac, 1997) or the self-administration of the heroin US (Lynch and Carroll, 1999;Carroll et al, 2002;Roth et al, 2002). In all of these studies, rats developed increasingly frequent lever-pressing as a function of experience with repeated pairings of lever CS with rewarding drug US.…”
Section: Sign-tracking Induced By Abused Drugsmentioning
confidence: 99%
“…Food restriction also elevates plasma corticosterone (Marinelli et al, 1996), which enhances the activity of the underlying dopaminergic reward system (Barrot et al, 2000;Marinelli and Piazza, 2002). Therefore, animals trained using food restriction demonstrated enhanced motivation (Carroll and Lac, 1993;Piazza and Le Moal, 1996) when nicotine first became available. This confounding factor precludes the possibility of attributing the acquisition of SA behavior to nicotine per se.…”
Section: Adolescent Nicotine Self-administration H Chen Et Almentioning
confidence: 99%